1995
DOI: 10.1093/oxfordjournals.aje.a117726
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Human Immunodeficiency Virus Seroconversion among Out-of-Treatment Drug Injectors in High and Low Seroprevalence Cities

Abstract: From 1988 to 1991, 6,882 drug injectors in 15 US cities were interviewed and had serum samples collected. The interviews and samples were analyzed for determination of significant predictors of human immunodeficiency virus (HIV) seroconversion in the 10 low seroprevalence cities and the five high seroprevalence cities. The unit of analysis was the period of observation between consecutive paired interviews/blood samples. In Cox proportional hazards regression, significant predictors of seroconversion in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 0 publications
5
64
2
3
Order By: Relevance
“…[11][12][13] As in those studies, IDUs in our study frequently reported needle sharing and other indirect sharing behaviors (more than 40%). These self-reported injection-related risk behaviors tended to be more common in Seattle and Los Angeles, where HIV infection was less prevalent.…”
Section: Discussionsupporting
confidence: 77%
“…[11][12][13] As in those studies, IDUs in our study frequently reported needle sharing and other indirect sharing behaviors (more than 40%). These self-reported injection-related risk behaviors tended to be more common in Seattle and Los Angeles, where HIV infection was less prevalent.…”
Section: Discussionsupporting
confidence: 77%
“…Injecting in public places has been associated with risky injection behaviors and HIV seroconversion in several studies [15,[35][36][37]]-a consequence of hurrying injection to minimize risk of police detection and arrest. This is a particularly common practice among homeless IDUs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 92% were male and 99% considered themselves Hispanic or Latino. Median age was 34 years [interquartile range (IQR): [28][29][30][31][32][33][34][35][36][37][38][39][40] and median time since first injection was 12.5 years (IQR: [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Study Populationmentioning
confidence: 99%
“…Also, the relatively low HIV prevalence in Atlanta (and even lower in Flagstaff) suggests that there might not be enough HIV present in networks (other than those of men who have sex with men) to use it to validate the risk index. Based on the arguments in Friedman et al 12 that HIV seroconversion is best predicted by membership in pockets of infection in cities with low HIV prevalence (whereas behaviors are good predictors where HIV prevalence is 20% or more), we would speculate that the HIV epidemic in Atlanta is still primarily confined to men who have sex with men. This, however, does not explain why this has been the case, how and if there might be an outbreak among IDUs, or how such outbreaks might be prevented.…”
Section: Network and Health: Five Papers That Show Some Of The Promimentioning
confidence: 94%